Sobre o conceito de acaso na filosofia de Charles S. Peirce - Salatiel, José Renato (2008)
The theme of this thesis is the concept of Chance in the philosophy of the American thinker Charles Sanders Peirce (1839-1914), a concept associated with the doctrine that he called Tychism. In this work, I propose to interpret different senses of the concept of chance that can be found in the work of the author, seeking to read them again in light of his philosophical system. I advocate, too, the hypothesis that Chance, one of the main concepts of peircean philosophy, must be interpreted from the systemic perspective of his work and in light of modern theories of complexity. I proposed, as a justification for this research, to make a contribution that will support an understanding of various aspects of peircean metaphysics, given the consideration that the concept of Chance, so present in contemporary scientific literature, is worked in an innovative and, we can say, pioneering way by the author. In the development of this work, I adopted, always, the criterion of reference to Peirce s original work, also referring to the scholarly literature concerning the theme in question